Unraveling the serial glycosylation in the biosynthesis of steroidal saponins in the medicinal plant Paris polyphylla and their antifungal action - Yuegui Chen; Qin Yan; Yunheng Ji; Xue Bai; Desen Li; Rongfang Mu; Kai Guo; Minjie Yang; Yang Tao; Jonathan Gershenzon; Yan Liu; Shenghong Li (Elsevier, 2023)
Sugar-sugar glycosyltransferases play important roles in constructing complex and bioactive saponins. Here, we characterized a series of UDP-glycosyltransferases responsible for biosynthesizing the branched sugar chain of bioactive steroidal saponins from a widely known medicinal plant Paris polyphylla var. yunnanensis. Among them, a 2'-O-rhamnosyltransferase and three 6'-O-glucosyltrasferases catalyzed a cascade of glycosylation to produce steroidal diglycosides and triglycosides, respectively. These UDP-glycosyltransferases showed astonishing substrate promiscuity, resulting in the generation of a panel of 24 terpenoid glycosides including 15 previously undescribed compounds. A mutant library containing 44 variants was constructed based on the identification of critical residues by molecular docking simulations and protein model alignments, and a mutant UGT91AH1Y187A with increased catalytic efficiency was obtained. The steroidal saponins exhibited remarkable antifungal activity against four widespread strains of human pathogenic fungi attributed to ergosterol-dependent damage of fungal cell membranes, and 2'-O-rhamnosylation appeared to correlate with strong antifungal effects. The findings elucidated the biosynthetic machinery for their production of steroidal saponins and revealed their potential as new antifungal agents.